Reply #2 to: Glycemic Choreoballism. (8th December 2016) - Roy, Ujjawal; Das, Shyamal Kumar; Mukherjee, Adreesh; Biswas, Debsadhan; Pan, Koushik; Biswas, Atanu; Panwar, Ajay
In Response To: Lee D, Ahn, TB. Glycemic choreoballism. Tremor Other Hyperkinet Mov. 2016; 6. doi:10.7916/D8QJ7HNF Original Article: Roy U, Das SK, Mukherjee A, et al. Irreversible hemichoreahemiballism in a case of nonketotic hyperglycemia presenting as the initial manifestation of diabetes mellitus. Tremor Other Hyperkinet Mov. 2016; 6. doi:10.7916/D8QZ2B3F